In situ generated hydrogen-bonding microenvironment in functionalized MOF nanosheets for enhanced CO 2 electroreduction - Ge Yang; Jiajia Huang; Weizhi Gu; Zhongyuan Lin; Qingyu Wang; Rong Kang; Jing-Yao Liu; Zhihu Sun; Xusheng Zheng; Long Jiao; Hai-Long Jiang (Proceedings of the National Academy of Sciences, 2025)
The microenvironment around catalytic sites plays crucial roles in enzymatic catalysis while its precise control in heterogeneous catalysts remains challenging. Herein, the coordinatively unsaturated metal nodes of Hf-based metal-organic framework nanosheets are simultaneously codecorated with catalytically active Co(salen) units and adjacent pyridyl-substituted alkyl carboxylic acids via a post modification route. By varying pyridyl-substituted alkyl carboxylic acids, the spatial positioning of the N atom in pyridine group relative to adjacent Co(salen) can be precisely controlled. Notably, the 3-(pyridin-4-yl)propionic acid, with para -position pyridine N atom, maximally improves the electrocatalytic CO 2 reduction performance of Co(salen) unit, far superior to other counterparts. Mechanism investigations reveal that the pyridine unit of 3-(pyridin-4-yl)propionic acid is optimally positioned relative to Co(salen) and undergoes in situ reduction to pyridinyl radical under working potentials. This greatly facilitates the stabilization of *COOH intermediate via hydrogen-bonding interaction, lowering the formation energy barrier of *COOH and therefore boosting CO 2 electroreduction.